Effect of Piper Betle Linn Extract on the Growth of Staphylococcus Aureus Atcc 25923 - Elfrida Elfrida; Erni Junaida; Raja Novi Ariska; Sri Jayanthi (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
Piper betle Linn or betel is a plant that is known to have antiseptic properties. The purpose of this study was to determine the effect of betel leaf extract (Piper betle Linn.) On Staphylococcus aureus ATCC 25923. The method used was an experimental method with a completely randomized design experimental design (CRD) using 2 methods, namely reflux and maceration methods, respectively. Each concentration of betel leaf extract (Piper betle L) which consists of one factor, namely the concentration of betel leaf extract (Piper betle L) with a variable factor level of betel leaf extract preparations of six treatments, positive, negative control and treatment 1%, 2%, 4% and 8%. By using betel leaf extract, 70% Methanol, distilled water and antibiotics. The results of the study the value of 1.650> 0.